What grass characteristics drive large herbivore feeding patch selection? A case study from a South African grassland protected area. Issue 4 (1st October 2020) - Mariotti, Elena; Parrini, Francesca; Louw, Cornelius J; Marshal, Jason P
Abstract : The coexistence of a large herbivore community depends on the degree of overlap in the resource used by the different species composing it. We investigated the role of grass greenness, height, biomass and feeding patch status on feeding patch selection by ruminant black and blue wildebeest ( Connochaetes gnou, Connochaetes taurinus ), red hartebeest ( Alcelaphus buselaphus ) and non-ruminant plains zebra ( Equus quagga ) in a protected grassland in South Africa. Selection by ruminants was associated with grass greenness and grass height, <10 cm for black and blue wildebeest, and >11 cm for red hartebeest. The non-ruminant zebra were more generalist, but selected for wetlands in all seasons, as did red hartebeest and blue wildebeest. Each species modified its behaviour during the late dry season by searching more for biomass or accepting grass that was less green or longer. The presence of burnt patches did not affect patch selection by any study species. Accordingly, large herbivore resource use showed strong seasonal adaptations, wetlands were important for sustaining sympatric species in the study area, and none of the species used the exact same combination of resources.